Factors Associated With Personal Hygiene and Sanitation Behavior of Food Handlers - Obby Hageng Priyambodho; Dwi Astuti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Food and drink are the most important necessities of life and can potentially be contaminated with pathogenic bacteria. One factor that influences food quality is the behaviour of food handlers in implementing personal hygiene and food sanitation. Several food handlers in Pengging Boyolali Square do not use aprons orneed to wash their hands when processing food ingredients. Vegetables, fish, shrimp and other food ingredients that will be cooked are not washed in running water, and there are still places to eat with poor hygiene and sanitation conditions. This research aims to determine the factors related to food handlers' personal hygiene and sanitation behaviour. This research is an analytical survey research using a cross-sectional study. This research will be conducted at Pengging Boyolali Field from September to October 2023. The population of this research is 100 food handlers with 80 samples. The research instrument uses a questionnaire through interviews and observations. Data analysis used bivariate analysis with the Chi-Square test. The results of the study showed that there was a significant relationship between knowledge and the personal hygiene and sanitation behaviour of food handlers (p-value=0.000; OR=7.792; 95%CI=2.403 - 25.777), there was a significant relationship between attitude towards personal hygiene and sanitation behaviour of food handlers (p-value=0.001; OR=6.548; 95%CI=2.098-20.431), and there is a significant relationship between work experience and personal hygiene and sanitation behaviour of food handlers (p-value=0.042; OR=2.886; 95%CI= 1,081-8,175). It is recommended that food handlers wear aprons and footwear when serving food and when processing food. Keywords: Attitude,Knowledge, Personal hygiene,Sanitation, Work period